Correlation analysis between EGFR gene mutation status, ALK positivity and demographic data, tumor biomarkers, radiological and pathological features in patients with lung adenocarcinoma - Zhang, Xue Fei; Zhang, Xu; Zhao, Liang; Zhao, Zhi Long (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to explore the relationship between EGFR mutations, ALK positivity, and demographic, tumor, radiological, and pathological characteristics in lung adenocarcinoma patients.MethodsThis study included 626 patients with early-stage lung adenocarcinoma who underwent surgical resection between October 2017 and December 2023.EGFR and ALK mutations were analyzed postoperatively. Clinical, pathological, and imaging features such as gender, age, smoking status, and tumor characteristics were assessed. Patients were categorized based on their mutation status, and comparisons were made regarding their clinical and imaging features.ResultsResults indicated that EGFR-positive patients were predominantly female, younger, and had a higher frequency of non-smokers compared to the wild-type (WT) group. EGFR mutations, particularly the exon 19 deletions and L858R mutations, were more common in patients with moderate differentiation and lepidic or acinar predominant histological subtypes. CT imaging revealed that EGFR-positive tumors were smaller in size and had fewer solid components compared to WT tumors. Additionally, certain CT features such as the spicule sign and air bronchogram were significantly associated with EGFR mutations. For ALK mutations, the analysis showed that patients with ALK-positive tumors had distinct radiological features, including a higher occurrence in the lower lobes and fewer ground glass nodules compared to the WT group.ConclusionsThe study concluded that specific radiological and pathological characteristics, along with EGFR and ALK mutation statuses, could be used to guide the treatment and diagnosis of lung adenocarcinoma.